Antisoviet proclamation, letter and writings - Jenciūtė, Viktorija (Genocidas ir rezistencija, 2021)
The article reviews the non-violent resistance of Lithuanian youth during the Soviet era in the Šiauliai region in the 1960sand 1980s, its expression and forms.
Keywords: soviet Lithuania; youth resistance; civil resistance; Šiauliai city; KGB